Analisis Kualitas Komunikasi dan Pelaksanaan Kerjasama terhadap Kepuasan Mitra di Perguruan Tinggi Farmasi - Pupu Fujriani Wasngadiredja; Wahyu Priyo Legowo (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This study aims to analyze the influence of communication quality and collaboration implementation on partner satisfaction in Tridharma Perguruan Tinggi cooperation at Sekolah Tinggi Farmasi Indonesia (STFI). The study employed a quantitative approach using a cross-sectional survey design. The population consisted of 54 domestic institutional partners actively involved in Tridharma collaboration activities in 2024, and all partners were included using a total sampling technique. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using validity testing, reliability testing, descriptive statistics, and multiple linear regression analysis. The results indicate that all research variables are categorized as very good, with mean scores above 4.50. Validity testing showed that all questionnaire items were valid, while reliability testing produced Cronbach’s Alpha values above 0.90, indicating excellent internal consistency. The regression analysis revealed that collaboration implementation significantly influences partner satisfaction (β = 0.543; p < 0.05), whereas communication quality has a positive but statistically insignificant effect (β = 0.220; p > 0.05). Simultaneously, communication quality and collaboration implementation significantly affect partner satisfaction. These findings demonstrate that the success of higher education partnerships is primarily determined by the quality of collaboration implementation, including professionalism, perceived benefits, and consistency with the Memorandum of Understanding (MoU). The study highlights the importance of implementation-based evaluation in strengthening sustainable institutional partnerships and improving the quality of Tridharma collaboration management in higher education institutions.